Dermatoscopy of infections and infestations - Manas Chatterjee; Shekhar Neema (Wolters Kluwer Medknow Publications, 2021)
Dermoscopy is a non-invasive tool for the diagnosis of skin diseases. Entomodermoscopy is a branch of dermoscopy that deals with infections and infestations. The use of dermoscopy for diagnosis of infections and infestations is rapidly increasing as it can provide useful clues related to diagnosis and effectiveness of treatment. It serves as a useful adjunct to microbiological and histopathological examination. In some cases, like scabies dermoscopy can even clinch the diagnosis.